2022
DOI: 10.1136/jech-2022-219676
|View full text |Cite
|
Sign up to set email alerts
|

Short-term exposure to ambient air pollution and readmissions for heart failure among 3660 post-discharge patients with hypertension in older Chinese adults

Abstract: BackgroundDespite ambient air pollution being associated with various adverse cardiovascular outcomes, the acute effects of ambient air pollution on hospital readmissions for heart failure (HF) among post-discharge patients with hypertension remain less understood.MethodsWe conducted a time-stratified case-crossover study among 3660 subjects 60 years or older who were admitted to hospital for HF after discharge for hypertension in Guangzhou, China during 2016–2019. For each subject, individualised residential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…A case-crossover Chinese study showed that short-term exposure to 23.3 μg/m 3 ambient SO 2 significantly increased the risk of HF readmissions by ∼15% among elderly patients with HTN. 44 …”
Section: Air Pollutionmentioning
confidence: 99%
“…A case-crossover Chinese study showed that short-term exposure to 23.3 μg/m 3 ambient SO 2 significantly increased the risk of HF readmissions by ∼15% among elderly patients with HTN. 44 …”
Section: Air Pollutionmentioning
confidence: 99%
“…In China alone, there are more than 245 million adults diagnosed with hypertension, resulting in medical expenditures exceeding 40 billion yuan per year [ 3 , 4 ]. Prior research has indicated that in 2017, the nationwide death toll attributed to hypertension reached 2.54 million, with years of life lost (YLL) due to premature mortality from hypertension at 3154.3 per 100,000 individuals, and years lost due to disability (YLD) at 428.0 per 100,000 individuals [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%